Streamlining of Bridge Piers as Scour Countermeasures: Effects of Curvature of Vertical Profiles. Issue 1 (January 2015) - Tao, Junliang; Li, Junhong
Pier streamlining is proposed as a flow-altering countermeasure to local scour for newly proposed piers. To obtain the optimal geometry, it is necessary to investigate the effect of the horizontal profile and vertical profile on the flow pattern around the piers. In a separate paper, the effect of the cross section was studied, and the optimal cross section was obtained. Continuing the effort, this paper investigates the effect of vertical profile curvatures. To achieve this goal, Bézier curves were used to parameterize the vertical curvatures. Fifty-one three-dimensional computational fluid dynamics models with different curvatures for the pier's vertical profile were constructed by varying the Bézier parameters and computed by COMSOL. All pier models in the flume had the same block ratio to ensure that results from test cases were comparable. Analysis and comparison of the simulation results showed that both a concave (or sloped) nose and a concave sidewall reduced the maximum shear stress around piers and that increasing the concave curvature of the sidewall enhanced the reduction effect. Increasing the concave curvature of the nose, however, tended to diminish the reduction effect. The practical implications from the findings are discussed in this paper.